Remain or return? An empirical study of influencing factors on the return of Chinese international students during the COVID-19 pandemic - Zhang, Keming; Zeng, Neng; Zhang, Kesen (Frontiers in Psychology, 2022)
Amid the COVID-19 pandemic, Chinese overseas students have been caught in a double bind over whether to return. Based on the Rational Choice Theory, this study used a mixed research method to explore the factors influencing their choices of returning. We constructed the influencing factors model, then developed a questionnaire and analyzed data from 1333 students using Binary Logistic Regression to examine the effect of influencing factors and their relationship with the choices of returning. Our findings show that survival rationality, institutional rationality, and development rationality have significant positive effects. Institutional rationality has the biggest promoting effect. Economic rationality is the biggest obstacle. We suggest that the Chinese government continue to implement effective epidemic prevention and control policies and seek a balance between epidemic prevention and socioeconomic development. The government should also actively optimize the development environment for overseas students, provide targeted assistance to them, and improve the quality of services.